1995
DOI: 10.1172/jci118092
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptides inhibit angiotensin II-induced proliferation of rat cardiac fibroblasts by blocking endothelin-1 gene expression.

Abstract: IntroductionThe present study was aimed to test the role of endothelin-1 (ET-1) as a possible autocrine/paracrine growth factor for cardiac fibroblasts, and to examine its interaction with cardiac natriuretic hormones. Expression of preproET-1 (ppET-1) mRNA by cultured cardiac fibroblasts from neonatal rats was demonstrated by Northern blot analysis using cDNA for rat ppET-1 as a probe. Although cardiomyocytes occupy -75% of the structural space of the heart, they constitute only one third of the total cell po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
140
2
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(151 citation statements)
references
References 33 publications
7
140
2
2
Order By: Relevance
“…Natriuretic peptides, NO, and cGMP-analogs have been shown to inhibit a number of important functions such as DNA synthesis and proliferation in cultured neonatal rat cardiac fibroblasts [32][33][34][35]. However the signalling pathway downstream of cGMP has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natriuretic peptides, NO, and cGMP-analogs have been shown to inhibit a number of important functions such as DNA synthesis and proliferation in cultured neonatal rat cardiac fibroblasts [32][33][34][35]. However the signalling pathway downstream of cGMP has not been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…For proliferation assays, mouse cardiac fibroblasts (passage 15-20 as well as passage [27][28][29][30][31][32][33][34][35][36][37][38][39] were seeded onto 12 well plates (Greiner, Frickenhausen, Germany) at a density of 500 cells/cm 2 . Subconfluent cells were starved in medium containing 0.1 % FCS for 2 days, then cell proliferation was stimulated for 48 h by the addition of fresh medium containing 5 % FCS in the presence or absence of 8-pCPT-cGMP (Biolog, Bremen, Germany).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…These peptides are produced by cardiomyocytes and activate a common guanylyl cyclase-coupled natriuretic peptide receptor subtype, guanylyl cyclase-A (GC-A) that is expressed in a wide variety of tissues, thereby leading to an increase in intracellular cGMP concentrations (3)(4)(5)(6)(7)(8). It was also demonstrated that the natriuretic peptide͞cGMP system might antagonize the proliferation and extracellular matrix production of cardiac fibroblasts through the inhibition of renin-angiotensin and endothelin systems (2,9,10). Synthesis and secretion of ANP and BNP are markedly augmented in patients with congestive heart failure and animal models of ventricular hypertrophy (4-6, 11, 12).…”
mentioning
confidence: 99%
“…Local ET-1 production in the heart has been reported, with secretion from the endocardium, myocardium, and coronary endothelium 1,2 and from cardiac fibroblasts. 3 ET-1 is generated by the conversion of 2 precursors, preproET-1 and proET-1. In the heart, this conversion is controlled by ET-converting enzyme (ECE), the membrane-bound isoform of which is named ECE-1.…”
mentioning
confidence: 99%